Moyamoya disease: diagnosis and interventions. Issue 8 (August 2022) - Ihara, Masafumi; Yamamoto, Yumi; Hattori, Yorito; Liu, Wanyang; Kobayashi, Hatasu; Ishiyama, Hiroyuki; Yoshimoto, Takeshi; Miyawaki, Satoru; Clausen, Tim; Bang, Oh Young; Steinberg, Gary K; Tournier-Lasserve, Elisabeth; et al.
Summary: Moyamoya disease is a rare cause of stroke, radiologically characterised by progressive stenosis of the terminal portion of the internal carotid arteries and compensatory capillary collaterals. The discovery that RNF213, which encodes an unconventional E3 ubiquitin ligase, is the major susceptibility gene for moyamoya disease in people from east Asia has opened new avenues for investigation into the mechanisms of disease and potential treatment targets. The Arg4810Lys variant of the gene is most strongly associated with moyamoya disease, but the penetrance is lower than 1%, suggesting a synergistic relationship with additional environmental and genetic risk factors. White people carry less common non-Arg4810Lys variants of RNF213, which partly explains the lower prevalence of moyamoya disease in European countries and in the USA than in east Asian countries. Several monogenic moyamoya syndromes possess the radiological characteristics of moyamoya disease and have been associated with multiple genes and pathways involved in moyamoya angiopathy pathogenesis. Further clarification of the genetic and environmental factors that contribute to the emergence of moyamoya angiopathy could enable development of new treatment strategies for moyamoya disease.